Stress Related Shift Toward Inflammaging in Cosmonauts After Long-Duration Space Flight - Buchheim, Judith-Irina; Matzel, Sandra; Rykova, Marina; Vassilieva, Galina; Ponomarev, Sergey; Nichiporuk, Igor; Hörl, Marion; Moser, Dominique; Biere, Katharina; Feuerecker, Matthias; Schelling, Gustav; Thieme, Detlef; et al. (Frontiers in Physiology, 2019)
Space flight exerts a specific conglomerate of stressors on humans that can modulate the immune system. The mechanism remains to be elucidated and the consequences for cosmonauts in the long term are unclear. Most of the current research stems from short-term spaceflights as well as pre- and post-flight analyses due to operational limitations. Immune function of 12 cosmonauts participating in a long-duration (>140days) spaceflight mission was monitored pre-, post-, and on two time-points in-flight. While the classical markers for stress such as cortisol in saliva where not significantly altered, blood concentrations of the endocannabinoid system (ECS) were found to be highly increased in-flight indicating a biological stress response. Moreover, subjects showed a significant rise in white blood cell counts. Neutrophils, monocytes and B cells increased by 50% whereas NK cells dropped by nearly 60% shortly after landing. Analysis of blood smears showed that lymphocyte percentages, though unchanged pre- and post-flight were elevated in-flight. Functional tests on the ground revealed stable cellular glutathione levels, unaltered baseline and stimulated ROS release in neutrophils but an increased shedding of L-selectin post-flight. In vitro stimulation of whole blood samples with fungal antigen showed a highly amplified TNF and IL-1 response. Furthermore, a significant reduction in CD4+CD25+CD27low regulatory T cells was observed post-flight but returned to normal levels after one month. Concomitantly, high in-flight levels of regulatory cytokines TGF-, IL-10 and IL-1ra dropped rapidly after return to Earth. Finally, we observed a shift in the CD8+ T cell repertoire towards CD8+ memory cells that lasted even one month after return to Earth. Conclusion: Long-duration spaceflight triggered a sustained stress dependent release of endocannabinoids combined with an aberrant immune activation mimicking features of people at risk for inflammation related diseases. These effects persisted in part 30 days after return to Earth. The currently available repertoire of in-flight testing as well as the post-flight observation periods need to be expanded to tackle the underlying mechanism for and consequences of these immune changes in order to develop corresponding mitigation strategies based on a personalized approach for future interplanetary space explorations.